“Ask, Acquire, Appraise”: A Study of LIS Practitioners Participating in an EBLIP Continuing Education Course - Sutton, Anthea; Booth, Andrew; Evans, Pippa (Evidence Based Library and Information Practice, 2013)
Objective – The project sought to examine the aspects of the question answering process in an evidence based library and information practice (EBLIP) context by presenting the questions asked, articles selected, and checklists used by an opportunistic sample of Australian and New Zealand library and information professionals from multiple library and information sectors participating in the “Evidence Based Library and Information Practice: Delivering Services That Shine” (EBLIP-Gloss) FOLIOz e-learning course. Methods – The researchers analyzed the “ask,” “acquire,” and “appraise” tasks completed by twenty-nine library and information professionals working in Australia or New Zealand. Questions were categorized by EBLIP domain, articles were examined to identify any comparisons, and checklists were collated by frequency. Results – Questions fell within each of the six EBLIP domains, with management being the most common. Timeliness, relevance, and accessibility were stronger determinants of article selection than rigour or study design. Relevance, domain, and applicability were the key determinants in selecting a checklist. Conclusion – This small-scale study exemplifies the EBLIP process for a self-selecting group of library and information professionals working in Australia and New Zealand. It provides a snapshot of the types of questions that library and information practitioners ask, and the types of articles and checklists found to be useful. Participants demonstrated a preference for literature and checklists originating from within the library and information science (LIS) field, reinforcing the imperative for LIS professionals to contribute to EBLIP research.